Efluxo de CO2 do tronco em árvores de uma floresta de terra firme na amazônia central - Borges, Edson Augusto Tavares Santiago (Instituto Nacional de Pesquisas da Amazônia - INPA, 2024)
The efflux of carbon dioxide in the tree trunk (Ea) represents a substantial fraction of the ecosystem's respiration. However, there are few studies that explain the effects of different plant functional characteristics on Ea rates, in addition to seasonality (dry and rainy seasons) and environmental factors in the Amazon. This is partly due to the great diversity of species and the challenges in setting up robust systems that are able to measure Ea with a high degree of efficiency under challenging environmental conditions such as the high humidity and intense rainfall events that occur in the Amazon. With this in mind, the aim of this dissertation was to study the dynamics of trunk CO2 efflux (Ea) in species with different wood densities during the dry and rainy seasons in an experimentally managed terra firme forest in the Central Amazon. The study was carried out at the Experimental Station for Tropical Silviculture, Nucleus ZF2, managed by the National Institute for Amazonian Research (INPA). For this study, a portable and dynamic measurement system was used to measure Ea variations in 30 trees of different species over a period of 8 months, distributed into 3 wood density classes (high, medium and low density). In order to standardize the Ea measurements, they were taken from each individual over a 24-hour period, at a high temporal frequency (measurements every 30 seconds), during the dry and rainy periods. The results obtained from this study showed that species with high wood density have higher Ea values in both seasonal periods when compared to species with low wood density. An inversely proportional relationship was found between Ea and trunk temperature. In addition, an inversely proportional relationship between Ea and xylem sap velocity was also observed for the high and medium wood density groups during the dry period, and for the low density group during the rainy period. A positive relationship was also found between the CO2 efflux in the trunk (Ea) and the water content in the surface layers of the soil. The variables total height (Ht) and diameter at breast height (DAP) of the trees selected for this study showed no correlation with Ea, while the variables Annual Periodic Increment (IPA) and crown diameter showed a low positive correlation with Ea. Finally, this study makes important contributions to a better understanding of CO2 dynamics in tropical forests and improvements to current climate models.
Keywords: Ecofisiologia vegetal; Mudança do clima; Respiração do tronco; Ciclo do Carbono